Designing rainwater harvesting systems integrating rainwater into building systems - Novak, Celeste Allen; Van Giesen, Eddie; DeBusk, Kathy M. (Wiley, 2014)
"Rainwater Harvesting the first comprehensive book on designing rainwater harvesting systems. It provides practical guidelines for developing a rainwater harvesting strategy, taking into account climate, public policies, environmental impact, and end uses. Case studies are included throughout, and a companion website houses worksheets, calculators, and other resources. Rainwater Harvesting is a valuable reference for architects, landscapes architect's, and site engineers" --Provided by publisher.